Constructing NiS2/CoS2/1T-MoS2-Sulfur Vacancy Catalyst to Boost Hydrogen Evolution Reaction and Oxygen Evolution Reaction - Li, Dan (Langmuir : the ACS journal of surfaces and colloids, 2025)
In this study, a dual-functional sulfur-vacancy-1T-MoS2/NiS2/CoS2 (NCM) electrocatalyst was successfully synthesized via a one-step hydrothermal method. Characterization results demonstrated that the unique morphology of the catalyst effectively prevented the agglomeration of MoS2 nanosheets. Furthermore, the introduction of Ni/Co has altered the electronic structure. Electrochemical performance tests revealed that the NCM catalyst exhibited outstanding hydrogen evolution reaction (HER) activity and oxygen evolution reaction (OER) performance. At a current density of 10 mA cm-2, the HER and OER overpotentials of this catalyst were only 72 and 296 mV, respectively, and it exhibited rapid reaction kinetics and stability for up to 12 h. The catalytic performance of NCM is significantly superior to that of its individual components, which is attributed to the synergistic interaction among the multiple components. This study provides a bimetallic MOF derivation strategy for the design of high-performance water splitting electrocatalysts